Islamic insurance in Indonesia: Future and prospects - Vinka Sindy Agustin (Universitas Sebelas Maret, 2020)
In Indonesia, insurance companies started operating in 1853 and are still experiencing ups and downs due to the emergence of various community movements. Insurance in Indonesia continues to grow, which is marked by the increasing number of insurance companies to more than 100 companies. Some of the insurance companies are categorized as Shariah or Islamic insurance. The purpose of this paper is to investigate the current condition of Islamic insurance in Indonesia and the prediction about its prospects and future. Using secondary data from various sources, we find that Islamic insurance in Indonesia has experienced a decline over the past year. One of the causes of the decline in the growth of Islamic insurance is the domino effect of the Covid-19 pandemic. In addition, Islamic insurance is also quite challenging to develop in Indonesia, even though the majority of the population is Muslim.